Optimizing Zakat Collection through Fintech: A SWOT Analysis and Digital Strategy in BAZNAS Jepara - Yuspita, Rinrin (Generate Digital Publishing, 2026)
Objective: This study aims to analyze the potential for and formulate strategies regarding the collection of zakat funds through the use of financial technology (fintech) at BAZNAS Jepara Regency, particularly in bridging the gap between the significant potential for zakat and the still suboptimal.Research Design & Methods: This research uses a qualitative approach with descriptive methods. Data were obtained through in-depth interviews with internal BAZNAS Jepara Regency officials, supported by documentation and literature review. Data analysis was conducted using a SWOT approach to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) in the implementation of fintech in zakat collection.Findings: The research results show that fintech has significant potential to increase zakat collection through ease of access, transaction efficiency, and expanded service reach. Its main strengths lie in the ease of digital payments and the substantial zakat potential, while weaknesses include low digital literacy and minimal outreach. Opportunities are driven by rapid technological developments and high internet usage, while threats include digital security risks and regulatory limitations. The resulting strategy includes integrating offline and online approaches, strengthening education and outreach, and developing collaborations with financial institutions and fintech platforms.Implications: These findings imply that optimizing fintech can be a strategic solution in increasing the effectiveness of zakat collection, expanding community participation, and increasing transparency and accountability in managing zakat funds.Contribution & Value Added: This research provides a contribution in the form of a zakat collection strategy model based on technology integration and a socio-educational approach, and produces strategic recommendations based on a SWOT analysis that can be used as a reference for developing more modern, inclusive and sustainable zakat management, especially at the regional level.